The Qualitative Evaluation Of Antibiotics Used In Pediatric Respiratory Tract Infection Treatments At A Primary Hospital In Surabaya - Ilil Maidatuz Zulfa (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2018)
Respiratory Tract Infections (RTIs) commonly occur as an infection in children. A considerable amount of antibiotics consumption is used to treat RTIs in many hospitals. Unwise antibiotic treatments in RTIs will increase bacterial resistance and treatment cost. This study aimed to investigate the quality or appropriateness of antibiotics use in RTI treatments in pediatric inpatients. A retrospective analysis of antibiotics consumption data was conducted through inpatient medical records for three months in 2017 at a primary hospital in Surabaya, Indonesia. The qualitative assessment was performed using a modified Gyssens algorithm based on the National Guideline and other relevant international standards of antibiotics applications in RTI treatment. The medical records of a total of 87 pediatric inpatients aged 0-14 y.o. were included in this study. The most common diagnosis was tonsillopharyngitis (32.18%), and the average length of hospital stay was 4.84 days. Antibiotics used in the treatments were from the class of -lactams and cephalosporins, all of which were applied in empirical therapy. According to the analysis, the antibiotic treatments were not appropriate. The most inappropriate use of antibiotics was in the form of wrong choice of drug choice (95.40%), followed by the sub-optimal duration of antibiotics (4.60%). The RTI treatment in pediatrics has to avoid any inappropriate uses of antibiotics, which can be achieved through the evaluation of institutional policy against the local guideline, antibiogram, or any relevant international guidelines.